Building Software - Krishnamurthy, Nikhilesh; Saran, Amitabh (Auerbach Publications, 2007)
Novel in its approach to software design, development, and management, Building Software: A Practitioner's Guide shows you how to successfully build and manage a system. The approach the authors recommend is a simple, effective framework known as Solution Engineering Execution (SEE). Through SEE, you create a successful solution by following a high.